Pragmatism and Its Contribution to English Language Teaching and Education - Vintoni, Aridem; Hadiyanto, Hadiyanto; Sulistiyo, Urip; Abrar, Mukhlas; Kuntarto, Eko (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
In the context of English language teaching and education, the philosophical foundation needs to be a concern and mastered by teachers or educators. The philosophical foundation of teaching and education is a set of assumptions that come from philosophy which is used as a starting point in teaching and education. This study aims to describe the concept of Pragmatism and its contribution to English language teaching and education. This study uses a qualitative approach with a library research method. The data were obtained from various scientific works related to the problem discussed in this study. The data were analyzed by using ‘content analysis’ technique. The findings showed that the philosophy of Pragmatism has given many contributions to English teaching and education; in terms of understanding the nature of learners or students, the goals of teaching and education, curriculum and teaching methods. According to the philosophical rationale of Pragmatism, curriculum and teaching methods can be developed in accordance with the learning objectives to be achieved.